Insights into degradation and targeting of the photoreceptor channelrhodopsin-1 - Wolfram, Michaela; Greif, Arne; Baidukova, Olga; Voll, Hildegard; Tauber, Sandra; Lindacher, Jana; Hegemann, Peter; Kreimer, Georg (Plant Cell and Environment, 2024)
In Chlamydomonas, the directly light-gated, plasma membrane-localized cation channels channelrhodopsins ChR1 and ChR2 are the primary photoreceptors for phototaxis. Their targeting and abundance is essential for optimal movement responses. However, our knowledge how Chlamydomonas achieves this is still at its infancy. Here we show that ChR1 internalization occurs via light-stimulated endocytosis. Prior or during endocytosis ChR1 is modified and forms high molecular mass complexes. These are the solely detectable ChR1 forms in extracellular vesicles and their abundance therein dynamically changes upon illumination. The ChR1-containing extracellular vesicles are secreted via the plasma membrane and/or the ciliary base. In line with this, ciliogenesis mutants exhibit increased ChR1 degradation rates. Further, we establish involvement of the cysteine protease CEP1, a member of the papain-type C1A subfamily. ΔCEP1-knockout strains lack light-induced ChR1 degradation, whereas ChR2 degradation was unaffected. Low light stimulates CEP1 expression, which is regulated via phototropin, a SPA1 E3 ubiquitin ligase and cyclic AMP. Further, mutant and inhibitor analyses revealed involvement of the small GTPase ARL11 and SUMOylation in ChR1 targeting to the eyespot and cilia. Our study thus defines the degradation pathway of this central photoreceptor of Chlamydomonas and identifies novel elements involved in its homoeostasis and targeting.
CRIS-Team Scopus Importer:2024-07-12
Keywords: ARL11; Calpain; CEP1; Chlamydomonas; cilia; cysteine proteases; extracellular vesicles; photoreceptor endocytosis; phototaxis; phototropin